Aprendizaje de educación sexual en estudiantes de octavo, noveno, y décimo año de educación general básica de la Unidad Educativa Particular Eloy Alfaro de Machala 2013-2014. - Bustamante Vidal, Jennifer Priscilia (2014)
Learning sexual education in adolescents is a topic of great interest since at this stage is where they will play the biological, psychological and social changes for which the young must have adequate knowledge of their reproductive organs and function the same to otherwise a biopsychosocial imbalance, generating this emotional conflict in young adolescents cause.